Mastering IDEAScript : the definitive guide - Mueller, John, 1958- (Hoboken, New Jersey : John Wiley & Sons, 2011)
'With approximately 44,000 users in the U.S. and Canada, as well as 42,000 in Europe, IDEA software has become a leading provider of data analysis software for use by auditors and accountants. Written to provide users with a quick access guide for optimal use of IDEAScript, Mastering IDEAScript: The Definitive Guide is IDEA's official guide to mastering IDEAScript, covering essential topics such as Introducing IDEAScript, Understanding the Basics of IDEAScript Editor, Designing Structured Applications, Understanding IDEA Databases and much more. For auditors, accountants and controllers.'--
Includes index.
Keywords: Auditing -- Data processing; Accounting -- Data processing; Scripting languages (Computer science); Data structures (Computer science)